Handbook of Georgian Literature - Ratiani, Irma, (Handbooks of Literary and Cultural Studies ;, 2025)
This Handbook of Georgian Literature is a philological study carried out by contemporary Georgian literary critics. This book traces the pivotal stages in the development of Georgian literature, showcasing not only its unique trajectory but also its deep connections to global literary currents. This study delves into the rich history of Georgian writing, tracing its evolution from the early Middle Ages to contemporary literary movements. Rejecting outdated Soviet methodologies that long skewed the perception of Georgian literature, the book reaffirms the deep-rooted connection between Georgian and European literary traditions. Alongside a sweeping overview, it offers detailed analyses of key periods, authors, and texts, shedding new light on the intellectual heritage of Georgian literature. While many women writers and poets played a significant role in shaping Georgian literature, their work has long been underappreciated in historical narratives. This book corrects that omission, giving these voices the recognition and space they deserve.